The German Bank Act of 1934: A Correction - Dessauer, M. (Review of Economic Studies, 1936)
I should like to correct an error which slipped into my article, “The German Bank Act of 1934,” in Vol. II, No. 3, of this Review, p. 217. The phrase, “This ratio also implies a limit, but in contrast to the cash ratio, it is a maximum limit” should read: “This ratio is imposed by the law as a minimum, as in the case of the cash ratio; but in reality it will figure as a maximum as long as the cash ratio is. far from being reached, and the assets forming this second line of defence will be the only means to fill up the first.” The remainder of the paragraph shows the reasons for this assumption.